TEACHERS' EXPERIENCES IN IMPLEMENTING THE INDEPENDENT CURRICULUM FOR STUDENTS WITH SPECIAL NEEDS AT MALIKA CENTER SPECIAL SCHOOL, WEST JAKARTA - Marselina Muda Bota; Joned Ceilendra Saksana; Muhammad Ramdhan (Journal Of Applied Multidisiplinary Studies, 2025)
This study aims to understand teachers' experiences in implementing the Independent Curriculum (Kurikulum Merdeka) at Malika Center Special School (SLB) in West Jakarta, which serves students with various special needs. The originality of this research lies in its focus on the context of inclusive education with a new and flexible curriculum approach. A qualitative method was employed, with data collection techniques consisting of in-depth interviews and classroom observations. Empirical results show that teachers welcomed the Independent Curriculum due to its flexibility in adapting learning to individual student needs. This curriculum allows for a more personal and relevant approach; however, its implementation faces challenges such as limited adaptive resources, high teacher workload, and the need for intensive communication with parents. Strategies implemented include comprehensive assessment, collaboration with experts, and the development of adaptive materials based on students' actual needs. The implications of this study indicate the need for further support from schools and the government in the form of ongoing training, inclusive policies, and the provision of adequate resources to support the successful implementation of the Independent Curriculum in special schools. This research provides an important contribution to the development of inclusive education based on the national curriculum